2022
DOI: 10.1002/sstr.202200011
|View full text |Cite
|
Sign up to set email alerts
|

Interface Modulation of FePc/Porous Ti(HPO4)2 Z‐Scheme Heterojunctions with Ultrafine Ag for Efficiently Photocatalytic CO Oxidation

Abstract: Herein, an integrative Z‐scheme heterojunction of ultrafine Ag‐ (≈ 4 nm) modulated FePc/porous Ti(HPO4)2 nanosheet (FePc/Ag/TiP NS) with extended spectrum response is designed and fabricated for efficient CO oxidation. The optimal one exhibits approximately tenfold enhancement in photocatalytic activity compared with the bulky TiP counterpart, even outperforming commercial TiO2 (P25). The greatly improved photoactivity is mainly ascribed to the accelerated Z‐scheme charge transfer, and well‐defined isolated ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…[15] Much research has focused on how to reduce the use of silver. [16][17][18][19] For example, Wang et al [17] prepared Ag-doped carbon quantum dots and found that a trace amount of Ag can achieve excellent antibacterial properties. Liang et al [18] prepared Pebax nanofiber-modified Ag nanoparticles and found that ultralow Ag loadings could effectively kill E. coli and S. aureus.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Much research has focused on how to reduce the use of silver. [16][17][18][19] For example, Wang et al [17] prepared Ag-doped carbon quantum dots and found that a trace amount of Ag can achieve excellent antibacterial properties. Liang et al [18] prepared Pebax nanofiber-modified Ag nanoparticles and found that ultralow Ag loadings could effectively kill E. coli and S. aureus.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely because of the low loading amount of Ag nanoparticles with high dispersion. 33,34 Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) studies were used to examine the microstructure and morphology of the resultant materials. CeO 2−x S x , as revealed by SEM images, possesses spherical structures with an average diameter of ∼500 nm (Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Notably, no obvious characteristic diffraction peaks related to Ag were found in 3Ag/CeO 2– x S x composites. This is likely because of the low loading amount of Ag nanoparticles with high dispersion. , …”
Section: Resultsmentioning
confidence: 99%
“…In a general way, constructing heterostructures is an effective strategy to promote the charge separation, which is a benefit for improving the performance of optoelectronic gas sensors. Significantly, 2D metal–organic frameworks (MOFs), that are composed of metal nodes and organic linkers and possess extremely large surface-to-volume ratio, ultrahigh porosity, and diverse structures, have been widely explored in various fields, such as gas storage and separation, catalysis, and chemical sensors. Especially, the 2D MOFs can be used to construct dimension-matched nanoheterojunctions with 2D CN nanosheets by the electrostatic induced-assembling strategy, which can shorten the charge diffusion distance from bulk to surface and thus reduce the recombination possibility of electron–hole pairs.…”
Section: Introductionmentioning
confidence: 99%